2018
DOI: 10.1016/j.oraloncology.2018.04.014
|View full text |Cite|
|
Sign up to set email alerts
|

The role of protein methyltransferases as potential novel therapeutic targets in squamous cell carcinoma of the head and neck

Abstract: Squamous cell carcinoma of the head and neck is a lethal disease with suboptimal survival outcomes and standard therapies with significant comorbidities. Whole exome sequencing data recently revealed an abundance of genetic and expression alterations in a family of enzymes known as protein methyltransferases in a variety of cancer types, including squamous cell carcinoma of the head and neck. These enzymes are mostly known for their chromatin-modifying functions through methylation of various histone substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
1
22
1
Order By: Relevance
“…HOTAIR knock‐down cells show decreased EZH2 with a significantly increased expression of E‐cadherin (Wu et al, ). This epigenetic mechanism of EZH2‐mediated silencing of E‐cadherin and subsequent enhancement of the migration and invasive properties of HNSCC cells has been observed in several independent studies (Saloura et al, ). Previous studies on TSCC showed a significant association between nodal stage and poor overall survival with reduced E‐cadherin expression due to overexpression of EZH2 (Wang, Liu et al, ).…”
Section: Ezh2 a Crossroad For Lncrna‐driven Interactions: Wnt/β‐catesupporting
confidence: 62%
“…HOTAIR knock‐down cells show decreased EZH2 with a significantly increased expression of E‐cadherin (Wu et al, ). This epigenetic mechanism of EZH2‐mediated silencing of E‐cadherin and subsequent enhancement of the migration and invasive properties of HNSCC cells has been observed in several independent studies (Saloura et al, ). Previous studies on TSCC showed a significant association between nodal stage and poor overall survival with reduced E‐cadherin expression due to overexpression of EZH2 (Wang, Liu et al, ).…”
Section: Ezh2 a Crossroad For Lncrna‐driven Interactions: Wnt/β‐catesupporting
confidence: 62%
“…Expression alteration in protein methyltransferases (PMTs) appears quite common among all head and neck SCCs. PMTs function to regulate epigenetic and transcriptional events typically by histone or non‐histone methylation which modifies protein interactions that may promote carcinogenesis (Saloura et al, ). The fact that KMT2C alterations were so common in our cohort and not in the comparator OCSCC cohort may indicate that KMT2C mutations represent an early alteration that is lost during clonal evolution to OCSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Although protein methyltransferases (PMTs) regulate epigenetic and transcription mainly through histone methylation, studies have also revealed some non-histone substrates methylated at lysine or arginine residues. It was shown that 95% of the HNSCC patients have genetic or expressional changes of PMTs (20). Based on these observations, PMTs might become a promising new anti-cancer target.…”
Section: Methylationmentioning
confidence: 97%
“…The nuclear receptor binding SET domain protein (NSD) family catalyzes the deposition of mono-and di-methyl groups on lysine 36 of histone H3 (H3K36me1, H3K36me2) (20). Loss of H3K36me2 caused by NSD1 inactivating mutations was shown to contribute to HNSCC (Fadu, PCI-4B, SCC4, SKN3) oncogenesis (21).…”
Section: Methylationmentioning
confidence: 99%